Rainfall and temperature variability in Bolivia derived from the tree-ring width of Amburana cearensis (Fr. Allem.) A.C. Smith - Paredes Villanueva, Kathelyn (2015)
Amburana cearensis is an important timber species in tropical lowland dry forests in Bolivia. We used dendrochronological methods to evaluate its climatic sensitivity and to identify its potential for the reconstruction of climate. For that, we collected eleven wood discs from randomly-selected mature trees. Despite the eccentricity of the discs and existence of false and wedging rings, all samples were successfully cross-dated. The average radial growth was 0.58cmyr-1. Significant correlation was found between the A. cearensis samples (0.34). Tree-ring width was positively correlated with monthly rainfall and negatively correlated with maximum temperatures during the 6-month rainy season (November-April). A. cearensis exhibits a potential for reconstructing climate in the Bolivian Chiquitania region.